2020
DOI: 10.3389/fimmu.2020.00806
|View full text |Cite
|
Sign up to set email alerts
|

Bcl6 Preserves the Suppressive Function of Regulatory T Cells During Tumorigenesis

Abstract: During tumorigenesis, tumor infiltrating regulatory T (Treg) cells restrict the function of effector T cells in tumor microenvironment and thereby promoting tumor growth. The anti-tumor activity of effector T cells can be therapeutically unleashed, and is now being exploited for the treatment of various types of human cancers. However, the immune suppressive function of Treg cells remains a major hurdle to broader effectiveness of tumor immunotherapy. In this article, we reported that the deletion of Bcl6 spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Moreover, BCL6 upregulates CXCR5 in Foxp3 + Treg cells, and thereby endows these so-called T follicular regulatory (Tfr) cells with the capacity to migrate towards the B cell follicular to limit the magnitude of GC responses ( 126 , 127 ). In addition, BCL6 maintains Foxp3 expression and promotes the suppressive ability of tumor-infiltrating Treg cells, and thus high BCL6 levels in Treg cells represent a poor prognosis marker in patients with colorectal cancer & melanoma ( 128 ). Of note, how BCL6 maintains the lineage stability and functional fitness of Treg cells specifically in tumor microenvironment remains unsolved.…”
Section: Zbtb Proteins Mainly Affecting the Function Of T Cellsmentioning
confidence: 99%
“…Moreover, BCL6 upregulates CXCR5 in Foxp3 + Treg cells, and thereby endows these so-called T follicular regulatory (Tfr) cells with the capacity to migrate towards the B cell follicular to limit the magnitude of GC responses ( 126 , 127 ). In addition, BCL6 maintains Foxp3 expression and promotes the suppressive ability of tumor-infiltrating Treg cells, and thus high BCL6 levels in Treg cells represent a poor prognosis marker in patients with colorectal cancer & melanoma ( 128 ). Of note, how BCL6 maintains the lineage stability and functional fitness of Treg cells specifically in tumor microenvironment remains unsolved.…”
Section: Zbtb Proteins Mainly Affecting the Function Of T Cellsmentioning
confidence: 99%
“…Consistent with our prediction, it has been confirmed that the downregulation of lncRNA GAS5 increases the binding of the transcription factor CEBPB to the promoter of GDF15 and promotes the progress and chemotherapy resistance of OC ( Guo and Wang, 2019 ). BCL6 is involved in regulating the immune response of tumor-infiltrating regulatory T cells during the occurrence and development of various tumors ( Li et al, 2020 ). CEBPA activation affected the regulation of immune-suppressive myeloid cells to cause antitumor response ( Hashimoto et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…4,5 In addition, Bcl6 seems to be expressed in Treg cell subsets other than Tfr cells especially those residing in parenchymal tissues and tumor. 23,24 Moreover, the microenvironment may affect the receptor expressions on Tfr cells, with an example that murine Tfr cells in the spleen have higher PD-1 but lower ICOS expressions as compared with those located in the draining lymph nodes (dLNs). 22 Collectively, identifications of Tfr cells solely via cytometric staining may be insufficient.…”
Section: Tfr Cell Definition Phenotype and Locationmentioning
confidence: 99%
“…For Bcl6, unlike Tfh cells where Bcl6 is crucial for cell development, the absolute dependence of Tfr cells on Bcl6 has been suggested but not strictly proved 4,5 . In addition, Bcl6 seems to be expressed in Treg cell subsets other than Tfr cells especially those residing in parenchymal tissues and tumor 23,24 . Moreover, the microenvironment may affect the receptor expressions on Tfr cells, with an example that murine Tfr cells in the spleen have higher PD‐1 but lower ICOS expressions as compared with those located in the draining lymph nodes (dLNs) 22 .…”
Section: Tfr Cell Definition Phenotype and Locationmentioning
confidence: 99%